In vivo visualization of murine melanoma cells B16-derived exosomes through magnetic resonance imaging - Liu, Tianqi; Li, Zhenlin; Li, Xiaodong; Zhao, Ruiting; Wei, Xinhua; Wang, Zixin; Xin, Sherman Xuegang (Biochimica et biophysica acta. General subjects, 2022)
Numerous studies demonstrated that exosomes play a powerful role in mediating intercellular communication to induce a pro-tumoral environment to promote tumor progression, including pre-metastatic niche formation and metastasis. Noninvasive imaging could determine the in vivo kinetics of exosomes in real time to provide better understanding of the mechanisms of the tumor formation, progression and metastasis. Magnetic resonance imaging (MRI) is an ideal technique which provides excellent anatomical resolution, intrinsic soft tissue contrast, unlimited penetration depth and no radiation exposure. A fusion protein composed of ferritin heavy chain (FTH1) and lactadherin was designed for visualizing exosomes through MRI. FTH1 was served as MRI reporter protein and lactadherin is a membrane-associated protein that is distributed on exosome surface. The characterizations of labeled exosomes were validated through transmission electron microscopy, western blot, nanoparticle tracking analysis and finally visualized in vitro and in vivo through MRI. MR imaging showed that the labeled exosomes are able to be visualized in vitro and in vivo. Verification of the characterizations of exosomes observed no significant difference between labeled and unlabeled exosomes. The proposed FTH1 labeling method was useful for visualizing exosomes through MRI. The present study first reported a novel self-label method for imaging labeled exosomes of tumor cells in vivo through MR with cell endogenous MRI reporter protein. It may be further used as a tool to enhance understanding the role of exosomes in various pathophysiological conditions. [Display omitted] •First time in vivo visualization of tumor cells' exosomes without MR contrast agent.•Exosomes could be self-labeled with endogenous MRI reporter protein.•Ferritin heavy chain (FTH1) label exosomes is noninvasively.•Labeling exosomes with FTH1 do not affect the characterizations of exosome.